Minimum Distance Calculation for Safe Human Robot Interaction - Safeea, Mohammad (2017)
The ability of efficient and fast calculation of the minimum distance between humans and robots is vitally important for realizing a safe human robot interaction (HRI), where robots and human co-workers share the same workspace. The minimum distance is the main input for most of collision avoidance methods, HRI, robot decision making, as well as robot navigation. In this study it is presented a novel methodology to analytically compute of the minimum distance between cylindrical primitives with spherical ends. Such primitives are very important since that there geometrical shape is suitable for representing the co-worker and the robots structures. The computational cost of the minimum distance between cylinders is of order. In this study QR factorization is proposed to achieve the computational efficiency in calculating the minimum distance mutually between each pair of cylinders. Experimental tests demonstrated the effectiveness of the proposed approach.